2012
DOI: 10.1016/j.jcrs.2011.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of deep anterior lamellar keratoplasty and intrastromal corneal ring segment implantation in advanced keratoconus

Abstract: Although DALK provided greater improvement in visual acuity and refractive errors in advanced keratoconus cases, ICRS implantation may be an alternative treatment with satisfactory outcomes and less visual impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 47 publications
1
30
0
1
Order By: Relevance
“…Other wise no statistically significant diffrence was found in the other parameters between both groups post operative. In comparing our results to Yusuf Ozerturk etal., (2012) [14] who compared these two techniques in moderate KC, we found that his results match with our study as he found that there was statistically significant improvement in all post operative parameters compared to the preoperative ones in both groups (UCVA,BCVA,SE and mean K value). in comparing the post operative results between the two groups , he found that there was statistically significant diffrence in all post operative parameters (UCVA,BCVA,SE and mean K value) with the upper hand to the DALK group and explained that by the fact that in DALK he removed the whole diseased tissue.…”
Section: Clarity Of the Corneasupporting
confidence: 88%
“…Other wise no statistically significant diffrence was found in the other parameters between both groups post operative. In comparing our results to Yusuf Ozerturk etal., (2012) [14] who compared these two techniques in moderate KC, we found that his results match with our study as he found that there was statistically significant improvement in all post operative parameters compared to the preoperative ones in both groups (UCVA,BCVA,SE and mean K value). in comparing the post operative results between the two groups , he found that there was statistically significant diffrence in all post operative parameters (UCVA,BCVA,SE and mean K value) with the upper hand to the DALK group and explained that by the fact that in DALK he removed the whole diseased tissue.…”
Section: Clarity Of the Corneasupporting
confidence: 88%
“…These patients received either ICRS implantation or deep anterior lamellar keratoplasty. ICRS effected a statistically significant increase in visual acuity (corrected and uncorrected distance visual acuity) from baseline to postoperative 24 months (p<0.001) (19) . Similarly, data from a study by El-Husseiny et al, which included 20 eyes of 16 patients, revealed that ICRS (Intacs, Addition Technology, Inc, Sunnyvale, CA) provided a viable alternative to early penetrating keratoplasty for patients with keratoconus having a clear central cornea and a history of contact lens intolerance.…”
Section: Discussionmentioning
confidence: 90%
“…In stable stages of the disease, the preservation of corneal thickness and transparency is crucial at the same time that the optical properties of the patient's own cornea are modified for improving visual acuity and quality of life. This has been attempted with corneal collagen crosslinking [25] and implantation of intracorneal ring segments [26], with very limited or unsuccessful outcomes. The application and implementation of femtosecond laser technology in ocular surgery deliver new opportunities regarding accuracy, programmability and predictability of surgical procedures, as well as an individual approach at the stage of planning and performing the operation [16].…”
Section: Discussionmentioning
confidence: 99%